Improving health clinic services through the application of QR code-based digital technology - Nursahidin Nursahidin; Gara Samara Brajadenta; Siti Jubaedah; Otto Fajarianto (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Public service is one of the benchmarks for evaluating the performance of a company or institution. The slow service process has a negative impact on the image of the government or company, in this case Public Health Services is no exception. This negative impact could have developed if not addressed immediately. Excellent, credible and efficient service is expected to be created within the Hasna Medika Group (Hospital Heart Clinic Network). By applying information technology in the service process, this really needs to be done. One solution to the above problems is to optimize the function of technology to speed up the service process. The technology that can be used is the application of the Quick Response (QR) Code as a medium that can be used by the public to simplify and speed up access to any information on Health Services at the Hasna Medika Group (Hospital Heart Clinic Network). The purpose of this research is to develop a service system for the Hasna Medika Group (Hospital Heart Clinic Network) by utilizing Android-based QR Code technology that can help speed up the service process to the public. The target of this research is the availability of public services based on QR Code technology with the Android operating system. The application of the QR Code is useful for displaying information in a mobile manner via a smartphone device. The use of the application is not restricted by space and time, so that the optimization of excellent service in units in the Hasna Medika Group (Hospital Heart Clinic Network) can be realized and become a positive image in society. The research method uses mix methods combining quantitative methods with qualitative methods consisting of secondary data collection and data analysis.